The nanoleakage phenomenon: influence of moist vs dry bonding - Pioch, Thomas; Staehle, Hans Jörg; Wurst, Marcus; Duschner, Heinz; Dörfer, Christof (The journal of adhesive dentistry, 2002)
To assess the degree of nanoleakage of Class V preparations restored with three bonding agents using wet and dry bonding. - Standardized Class V cavities were prepared in 66 human molars with cervical margins located in dentin.
Gesehen am 24.03.2021